Glow Discharge Plasma Modified Surfaces for Hepatic Co-culture Models - Ramírez-Fernández, O; Godínez, R; Morales, J; Gómez-Quiroz, L; Gutiérrez-Ruiz, M C; Zúñiga-Aguilar, E; Olayo, R (Revista Mexicana de Ingenieria Biomedica, 2012)
The aim of the development of Bioartificial livers (BAL) is to create biological models that imitate the liver function. In recent years improvements in these models have been obtained by using cocultures of structured and parenquimal cells. The cell adhesion is fundamental to generate a cell culture, for this reason, we used biocompatible materials or biocompatible polymers synthesized by plasma discharge. In this work we used a polypyrrole doped with iodine (Ppy-I) cell culture surface, synthesized by plasma glow discharge to cultivate hepatocytes of the cell line HepG2 with immortalized stellate or Ito cells. These cocultures were compared to a standard surface cell culture. We analyzed the morphology and cell proliferation during 9 culture days. Also, we analyzed the whole supernatant protein secreted, the results show an increase in the secreted protein when we used the Ppy-I in comparison to the standard surface, we obtained maximums of 8 μg/ml and 6 μg/ml respectively. We didn’t observed morphological differences between the Ppy-I surface and the standard surface. We conclude that the hepatic cell cocultures on a Ppy-I surface, stimulates the hepatic secreted protein. These results can be used to improve the performance of BAL.